Changes of thoracic duct flow and morphology in an animal model of elevated central venous pressure - Lu, Xiao; Wang, Mengjun; Han, Ling; Krieger, Joshua; Ivers, Jillian; Chambers, Sean; Itkin, Max; Burkhoff, Daniel; Kassab, Ghassan S. (Frontiers in Physiology, 2022)
Objective: Investigation of lymph fluid dynamics in thoracic duct during central venous pressure elevation. Background: Lymphatic flow is affected by elevated central venous pressure (CVP) in congestive heart failure. The changes of thoracic duct (TD) lymph flow have not been studied chronically in the setting of elevated CVP. This study is to investigate fluid dynamics and remodeling of the TD in the elevated CVP animal model. Methods: A flow probe was implanted on the swine TD (n = 6) and tricuspid regurgitation (TR) was created by cutting tricuspid chordae percutaneously. Six swine were used as control group animals. The TD flow was measured for 2 weeks (baseline) before TR and 4 weeks postop-TR surgery. Arterial pressure and CVP were measured. The pressure and flow in the TD were measured percutaneously. Histological and morphological analyses were performed. Results: TR resulted in an increase in CVP from 4.2 ± 2.6 to 10.1 ± 4.3 mmHg (p < 0.05). The lymph flow in the TD increased from 0.78 ± 1.06 before TR to 8.8 ± 4.8 ml/min (p < 0.05) 2 days post-TR and remained plateau for 4 weeks, i.e., the TD flow remained approximately 8–11 fold its baseline. Compared to the 8.1 ± 3.2 mmHg control group, the TD average pressures at the lymphovenous junction increased to 14.6 ± 5.7 mmHg in the TR group (p < 0.05). The TD diameter and wall thickness increased from 3.35 ± 0.37 mm and 0.06 ± 0.01 mm in control to 4.32 ± 0.57 mm and 0.26 ± 0.02 mm (p < 0.05) in the TR group, respectively. Conclusion: The elevated CVP results in a significant increase in TD flow and pressure which causes the TD’s outward remodeling and thickening. Our study implicates that the outward remodeling may result in the TD valve incompetence due to failure coaptation of leaflets.